The Complete Mitogenome of Elymus sibiricus and Insights Into Its Evolutionary Pattern Based on Simple Repeat Sequences of Seed Plant Mitogenomes - Xiong, Yanli; Yu, Qingqing; Xiong, Yi; Zhao, Junming; Lei, Xiong; Liu, Lin; Liu, Wei; Peng, Yan; Zhang, Jianbo; Li, Daxu; Bai, Shiqie; Ma, Xiao (Frontiers in Plant Science, 2022)
The most fascinating characteristics of plant mitochondrial genomes (mitogenomes) include their high variation in sequence and structure, horizontal transfer (HGT) feature and their important role in hypoxic adaptation. However, further investigation of the mechanisms in hypoxic adaptation and HGT of plant mitochondria remains challenging due to the limited sequenced mitogenomes and non-function of the transferred DNA. Here, the mitogenome of Elymus sibiricus (Gramineae, Triticeae), a perennial grass species native to Qinghai-Tibet plateau (QTP) was de novo assembled and compared with a further eight Gramineae species. The unique mitochondrial evolution pattern of E. sibiricus reflected by the lowest RNA editing frequency, highest Ka/Ks values and unique haplotype composition of the shared genes in Gramineae species may attribute to the long-term plateau adaptability of E. sibiricus. Especially the strong positive selection between E. sibiricus and other Gramineae species was observed in the two cytochrome C synthesis genes ccmB and ccmC. We aimed to discover the connection between mitogenome SSRs (mt - SSRs) and HGT. Therefore, we predicted and annotated the mt - SSRs of E. sibiricus along with other sequenced 87 seed plants. The clustering result based on all the predicted compound mitogenome SSRs (c – mt - SSRs) revealed the obvious synteny correlation within systematic taxa and also in inter-taxa. The c – mt - SSRs were annotated to 11 genes, among which ‘(ATA)3agtcaagtcaag(AAT)3’ occurred in the nad5 gene of 8 species. The results above - mentioned further confirmed the sequence HGT of mitogenomes among even distant species from the perspective of c – mt - SSRs. Two genes nad4 and nad7 possessed the vast number of SSRs in their intron regions across the seed plant mitogenomes. Furthermore, five pairs of SSRs developed from the mitogenome of E. sibiricus could be considered as the potential markers for species distinguish between E. sibiricus and its related sympatric species E. nutans.